Fair Isaac Introduces Payment Optimizer 2.0 to Increase Fraud Detection Capabilities for Healthcare Payers (Business Wire, 2004)
Fair Isaac healthcare analytics deliver proven solutions that unlock value and improve decision making for healthcare payers and providers. Analyzing over 600 million claims each year, the company's solution identify fraudulent or erroneous healthcare claims before payment is issued, without slowing claims process and payment systems or violating prompt-pay legislation. Fair Isaac's healthcare analytics suite is based on advanced and patented neural network modeling and dynamic profiling technologies, which Fair Isaac introduced in the financial services industry. These innovations have transformed the industry's approach to fighting fraud, helping lenders reduce fraud losses by as much as 50 percent. The healthcare solutions suite extends beyond fraud detection to include collections and recovery, consumer behavior, customer relationship management, data cleansing, enterprise decision management and pharmaceutical marketing. Fair Isaac's healthcare experts provide hands-on customer service and training, earning high customer satisfaction ratings. Except for historical information contained herein, the statements contained in this press release that relate to Fair Isaac, including statements regarding its Payment Optimizer 2.0 product offering and the benefits to be derived from this offering, are forward-looking statements within the meaning of the "safe harbor" provisions of the Private Securities Litigation Reform Act of 1995. These forward-looking statements are subject to risks and uncertainties that may cause actual results to differ materially, including any unforeseen technical difficulties related to the implementation, use and functionality of the offering, the risks that customers will not perceive material benefits from the offering, failure of the product to deliver the expected results, the possibility of errors or defects in the offering, regulatory changes applicable to the use of consumer credit and other data, and other risks described from time to time in Fair Isaac's SEC reports, including its Annual Report on Form 10-K for the year ended September 30, 2003, and quarterly report on Form 10-Q for the period ended March 31, 2004. Forward-looking statements should be considered with caution. If any of these risks or uncertainties materializes or any of these assumptions proves incorrect, Fair Isaac's results could differ materially from Fair Isaac's expectations in these statements. Fair Isaac disclaims any intent or obligation to update these forward-looking statements.